The influence of feed protein level on some productive indices in Barred Plymouth Rock reared in free range system - Simiz Eliza (Review on agriculture and rural development, 2014)
The purpose of this paper was to assess the possibility of grow mixed breed broilers in free range system fed according to the slow feeding rate, with nutritional requirements mainly consisting of feed concentrate mixtures starting from the premises that currently there are no nutritional standards especially created for maintenance alternative systems. The experiment for the quantification of impact of nutritional features and of the CM administration intake on bio productive and economic performances of Barred Plymouth Rock avian youth has been reared during 10 weeks on two experimental variants. The elaborated experimental design was intended to assess the effect of a good nutritional start in both variants, but with a different time. Considering the same start, both in Vi and V2, by administering an CM with 2960 kcal ME and 22.04% CP, for 14 days in V| and 21 days in V2.Vi received a tri-phase feeding by using an intermediary „growing" phase during 36 days when CM was administered with 2990 kcal ME/kg and 20.03% CP followed by a finishing phase after 50 days and continued until the end of experiment, when CM was administered with 3000 kcal ME/kg and 17.30% CP. V2 was intended to establish the effect of a bi-phase feeding, therefore phase II became the „growing-finishing" phase, respectively the administration of a feed concentrate mixture with an energy level of 3000 kcal ME and 17.30% CP. Broilers in V,, tri-phase fed, had a feed intake comparison with that of broilers in V2 (bi-phase fed), an average body weight of 1428.60 g with a total increase of 8.3% higher and a better feed conversion (2.66 kg/kg) considering the increased costs per kg of live mass with 1.87% comparing with V2. Regarding the CP intake, depending on ME intake, the registered values are close in both variants. Based on a mathematic model like: y = a/(l+bx+cx2 ), one can assess the fodder feeding costs. The correlation rate between the fodder feeding costs and the CP intake is strongly positive for both variants.